2021
DOI: 10.1002/sdtp.15238
|View full text |Cite
|
Sign up to set email alerts
|

55.1: Invited Paper: FMM‐free OLED Manufacturing Enabled by Photolithographic Patterning Processes

Abstract: Resolution and brightness are the essential figure‐of‐merits for the microdisplay development needed for AR and VR applications. In this presentation, we show our technology development toward high‐resolution FMM‐free direct R‐G‐B OLED microdisplays. We show the schematic fabrication setup and integration route to fabricate red, green, and blue OLED pixels side‐by‐side by the OLED photolithographic patterning processes. We demonstrate a 1µm line and space feature with the photoresist and transfer the pattern t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…f Comparisons of the previously reported resolution of full-color OLED arrays with our work (refs. 45 55 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…f Comparisons of the previously reported resolution of full-color OLED arrays with our work (refs. 45 55 ). …”
Section: Resultsmentioning
confidence: 99%
“…4d). Thanks to this superior patterning capability of the SI-OLES, furthermore, the full-color SI-OLED array corresponding to 949 ppi was successfully achieved, exhibiting the highest resolution compared to the reported full-color OLED arrays via various OLED patterning methods [45][46][47][48][49][50][51][52][53][54][55] (Fig. 4e, f and Supplementary Fig.…”
Section: Demonstration Of High-resolution Full-color Si-oledsmentioning
confidence: 88%
“…Current methods for S×S organic device patterning include vacuum deposition through fine metal shadow masks, direct patterning via organic vapor-jet printing, solution processing using ink-jet printing or microchannels, film transfer via laser-induced thermal imaging, and postdeposition processing via chemical lift-off. A somewhat less complex and damage-free method that can achieve photolithographic resolution is mechanical peel-off, which has recently been demonstrated for patterning organic photovoltaics and perovskite light-emitting devices. , In this work, we demonstrate two-color, S×S WOLEDs deposited via vacuum thermal evaporation and subsequently patterned using mechanically peeled-off films. This method allows for multilayer patterning with micron-scale resolution while avoiding precise alignment of shadow masks, or exposing the individual color-emitting stripes to destructive solvents used in conventional photolithography.…”
Section: Introductionmentioning
confidence: 99%
“…The color filter method has a decrease in brightness due to the device structure [16]. Fine metal mask and photolithography methods, which are direct patterning methods, also accompany a shadow effect from the distance between substrates [17,18] and chemical limitations such as damage to organic materials caused by process characteristics [19,20]. In our previous research, we showed the possibility of fabricating high-resolution patterns with high stability through solution and evaporation hybrid technology [4,21,22].…”
Section: Introductionmentioning
confidence: 99%